Efficient Asymmetric Synthesis of Structurally Diverse P‐Stereogenic Phosphinamides for Catalyst Design1. (10th March 2015) - Han, Zhengxu S.; Zhang, Li; Xu, Yibo; Sieber, Joshua D.; Marsini, Maurice A.; Li, Zhibin; Reeves, Jonathan T.; Fandrick, Keith R.; Patel, Nitinchandra D.; Desrosiers, Jean‐Nicolas; Qu, Bo; Chen, Anji; et al.
Abstract The use of chiral phosphinamides is relatively unexplored because of the lack of a general method for the synthesis. Reported herein is the development of a general, efficient, and highly enantioselective method for the synthesis of structurally diverse P‐stereogenic phosphinamides. The method relies on nucleophilic substitution of a chiral phosphinate derived from the versatile chiral phosphinyl transfer agent 1, 3, 2‐benzoxazaphosphinine‐2‐oxide. These chiral phosphinamides were utilized for the first synthesis of readily tunable P‐stereogenic Lewis base organocatalysts, which were used successfully for highly enantioselective catalysis.